Crimean-Congo Haemorrhagic Fever: A Potentially Fatal Outbreak in Pakistan - Imran Karim, Muhammad Iqbal Shah, Syed Zulfiquar Ali Shah, Shagufta Laila Memon, Allah Warayo Kanhyoon,Shafaq Jabeen, Syed Jahanghir, Samar Raza (Pakistan Journal of Medical & Health Sciences, 2024)
Africa, the Balkans, parts of the Middle East, and Asia are endemic for tick-borne Crimean-Congo hemorrhagic fever (CCHF)1. The disease is more common in persons infected with Hyalomma ticks or who come in contact with sick cattle tissues after slaughter2. The virus, which has a high case-fatality rate, can cause epidemics in anyone who comes across infected bodily fluids and has caused health facility outbreaks.3The four illness load in Pakistan includes transmissible, not transmissible, mental disorders, and accidents. Additionally, some rising health problems are straining limited national healthcare resources. A good instance is Crimean-Congo Haemorrhagic Fever (CCHF).CCHF-endemic countries fight the infection. A World Health Organisation statement stated that roughly 212 instances, 27 of them life-threatening, were documented in Iraq in 2022 among different governorates. CCHF-free nations still test ticks for the disease4. The Ministry of Health in France found the very first CCHF in Hyalomma ticks from livestock in the southern Eastern Pyrenees5. Ticks have been reported in the Mediterranean coast, especially Corsica. Spain has documented domestically acquired illnesses in humans since 2016, including in medical practitioners6. The first documented CCHF patient in Pakistan was identified in 1976, with the following isolated instances and epidemics7.